If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(7 + -1x) = x + 2 (7 * -1 + -1x * -1) = x + 2 (-7 + 1x) = x + 2 Reorder the terms: -7 + 1x = 2 + x Solving -7 + 1x = 2 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -7 + 1x + -1x = 2 + x + -1x Combine like terms: 1x + -1x = 0 -7 + 0 = 2 + x + -1x -7 = 2 + x + -1x Combine like terms: x + -1x = 0 -7 = 2 + 0 -7 = 2 Add '7' to each side of the equation. -7 + 7 = 2 + 7 Combine like terms: -7 + 7 = 0 0 = 2 + 7 Combine like terms: 2 + 7 = 9 0 = 9 Simplifying 0 = 9 Combine like terms: 0 + -9 = -9 -9 = 9 + -9 Combine like terms: 9 + -9 = 0 -9 = 0 The solution to this equation could not be determined.
| 15x=6(x-9) | | 4(-3x+1)=-10x(x-4)-14x | | 10-(10-y)=21-2y | | (9x+3x)-(4x^2+8x)= | | 11=u-1 | | (8x^2+1)+(12x^2+6)=0 | | t^2+25t-24=0 | | 3[w-1]=2w-6 | | w=zr-4zc^4 | | a^8-7a^7+a-7=0 | | 3(y-2)-5y=-2(y+2) | | 2x+3=a | | (3+5x)(4-x)= | | d+(0.8)=4.0 | | P^2=10-9P | | 3x^2-12Y^2=0 | | 5p+2-3p=8+4p-6 | | (2y-1)(2y+1)= | | 4x+-3=2x+-12 | | -3y+3-2y=-8+2y | | -1+2=12 | | 5x^2(4x^3+10x)=0 | | .0002x^2-.316x+135.9=0 | | 4(x-2)(x+3)= | | X-a=b | | 14x=-10 | | -6.2+11.4=25 | | 5x(2x-1)-14=2x(5x+6)+3 | | 12x^2-36x-21=0 | | 9(x-3)=2(5x-1) | | 3-6y=12+18y | | 125=(4r+2)+(5r-12) |